Resonant tunneling diode oscillators for optical communications - Watson, Scott (2018)
The ability to use resonant tunneling diodes (RTDs) as both transmitters and receivers is an emerging topic, especially with regards to wireless communications. Successful data transmission has been achieved using electronic RTDs with carrier frequencies exceeding 0.3 THz. Specific optical-based RTDs, which act as photodetectors, have been developed by adjusting the device structure to include a light absorption layer and small optical windows on top of the device to allow direct optical access. This also allows the optical signal to directly modulate the RTD oscillation. Both types of RTD oscillators will allow for seamless integration of high frequency radio and optical fiber networks.